Community Structure along Timberline Ecotone in Relation to Micro-topography and Disturbances in Western Himalaya - Ishwari D. RAI; Bhupendra S. ADHIKARI; Gopal S. RAWAT; Kiran BARGAL (Notulae Scientia Biologicae, 2012)
Four communities, formed as a result of locally varying site conditions, were identified and studied along the timberline ecotone in part of Kedarnath Wildlife Sanctuary (KWS). Communities on the vicinity of pilgrimage site and along gentler slopes were highly disturbed having sharp timberlines, while those located far and in the steep slopes were less affected, forming a little broader transition. The tree density ranged from 340 to 780 trees/ha, while the basal cover of communities varied greatly and ranged from 6.4 to 55.1 m2/ha. Birch dominated community had lowest basal area among all the communities, while mixed community had the highest. In all the respective communities, from subalpine zone, density and basal area was higher than that of timberline zone. The Importance Value Index (IVI), which used to determine the overall importance of each species in the community structure, of dominant species at timberline was more than 200 in all the communities, except in the mixed community. Influence of the anthropogenic disturbances was apparent on the regeneration performance of all the studied tree species. Rhododendron campanulatum was the dominant shrub species of the area and formed krummholz, while distribution of other species varies greatly with forest type. The shrub density decreased from high to low disturbance, while the herbaceous species density increased with prevalence of a few species favoring the high disturbance (grazing). The shrub and herb species richness was higher in the ecotone zone. Some uncommon species like Balanophora involucrata and Aralia cissifolia were also found at timberline. Three species of Ladys Slipper orchid were reported together from Betula utilis community at timberline ecotone.